Cisplatin-Induced Rodent Model of Kidney Injury: Characteristics and Challenges. (12th September 2018) - Perše, Martina; Večerić-Haler, Željka
Abstract : Cisplatin is an antitumor drug used in the treatment of a wide variety of malignancies. However, its primary dose-limiting side effect is kidney injury, which is a major clinical concern. To help understand mechanisms involved in the development of kidney injury, cisplatin rodent model has been developed. Given the complex pathogenesis of kidney injury, which involves both local events in the kidney and interconnected and interdependent systemic effects in the body, cisplatin rodent model is indispensable in the investigation of underlying mechanisms and potential treatment strategies of both acute and chronic kidney injury. Cisplatin rodent model is well appreciated and widely used model due to its simplicity. It has many similarities to human cisplatin nephrotoxicity, which are mentioned in the paper. In spite of its simplicity and wide applicability, there are also traps that need to be taken into account when using cisplatin model. The present paper is aimed at giving a concise insight into the complex characteristics of cisplatin rodent model and heterogeneity of cisplatin dosage regimens as well as outlining factors that can severely influence the outcome of the model and the study. Challenges for future research are also mentioned.